Nong Chok Muslim Students’ Perspective on LGBTQ+ Rights Legalization - Zidan, Muhammad Zainuddin; Zaini Tamim AR (Jurnal Pendidikan Islam Indonesia, 2025)
Thailand is the only Southeast Asian country that is highly progressive in advancing the legalization of same-sex marriage. This development has elicited responses from various segments of society, including Muslim students as part of the minority group. This study examines the perspectives of Muslim students in Bangkok on the increasingly prominent issue of same-sex marriage legalization in Thailand, focusing on their viewpoints, socio-religious aspects, and the influence on their attitudes. The research employs a descriptive quantitative method. Data were collected from 18 Muslim students at an Islamic-based public school in Bangkok using a five-point Likert scale questionnaire. The findings reveal that Islamic values serve as the primary foundation shaping the views and attitudes of Muslim students in rejecting the legalization of same-sex marriage. However, they also exhibit a tolerant attitude in their interactions with LGBTQ+ individuals or communities, reflecting a pluralistic stance as citizens of Bangkok. The implications of this study highlight the importance of Islamic education that integrates Islamic values with pluralism, enabling Muslim students to adapt to a diverse society. Additionally, it offers an academic contribution to the literature on the relationship between religion and pluralism in the context of religious minorities.